Perhitungan Simpanan Karbon Atas Permukaan di Hutan Lindung KPHP Meranti untuk Mendukung Program Redd+ - Yuningsih, Lulu; Lensari, Delfy; Milantara, Noril (Fakultas Kehutanan Universitas Jambi, 2018)
The Red River Protected Forest is close residential areas, resulting in intensive interactions between communities and protected forest. Directed on the management, extracting forest products not wood and services environment. One management services environments that are going to a business and can be administered in the forest are participating in the scheme incentives services mechanism store and carbon spare. When management will follow the incentives stock and absorb carbon REDD+, so then calculation carbon stock early to important and necessary. This study aims to calculate the amount of savings mobilized carbon the upper surface of the in a protected forest the red river KPHP Meranti. The value of the amount of savings mobilized carbon the above ground of them in the long term, can be used as a baseline to participate in the program REDD+. The data stands in the form of a stake through the stake, with a pole and trees in every type veils and the diameters of tree height measurement (DBH) taken from secondary data the results of previous studies that will be used as a means of calculation stands biomass. The result of this research is saving through the largest carbon in the field were in the protected land cover of secondary 259.3474 Ton/C, second largest carbon savings are covered land shrub with the saving of carbon stock 21.8023 T/c and the smallest carbon stock is in plantations by land cover the carbon stock of 6.2881 Ton/C.